MEANING AND ESSENCE OF CIVIL SOCIETY: THEORETICAL AND CONCEPTUAL APPROACHES - Skyba, Maryna (Public Management and Policy, 2025)
Reconstruction of Ukraine on a democratic basis requires a policy grounded in scientific research. It needs fundamental scientific research on themes of civil society, which accounts for geopolitical and strategic realities and risks. The main goal of research is to propose the theoretical concept of “civil society” and the main scientific approaches in civil society. The goal of the research was achieved in the process of scientific research in the form of realizing tasks. The main scientific methods were used in the article to conduct research. The author used general scientific research methods: the method of scientific cognition, scientific abstraction, analysis, and generalization, etc. The author used an interdisciplinary approach to define the concept of civil society. “Civil society” is system (sphere) consisting of associations, organizations, people (individuals) who interact based on unity of beliefs, value orientations, chosen moral and political goals, which, by the power of legal mechanisms (norms of national and international law), guarantees each individual the free choice of their economic existence, affirms the priority of human rights, excludes the monopoly of one ideology, one worldview, guarantees freedom of conscience, and stands in defense of individual, collective, and social needs. The author offers the following main scientific approaches to understanding the essence and content of civil society: socio-philosophical, philosophical, legal, historical, political science, and economic. The informational, financial, psychological, environmental, geographical, cultural, national security, and other approaches can also be used to understand the essence of civil society, but these aspects are not included in the scope of this author’s research. The author also emphasizes that some aspects of the development of civil society in the face of today’s challenges have not been sufficiently covered in the scientific works of Ukrainian and foreign scientists and require further research.